2022
DOI: 10.22175/mmb.13017
|View full text |Cite
|
Sign up to set email alerts
|

2018 National Beef Flavor Audit: Consumer and Descriptive Sensory Attributes

Abstract: Beef flavor has been identified as a driver of consumer acceptability; however,  little is known about variability of flavor in major retail beef cuts. Four beef cuts (chuck roast = 50, top sirloin steaks = 49, top loin steaks =50, and 80/20 ground beef = 50) were obtained from retail stores in Miami, Los Angeles, Portland, New York, and Denver during a two-month period in 2018. Beef present in the retail beef cases were purchased to be representative of consumer selections.  Production syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…On the other hand, chuck steaks had the lowest scores for all sensory attributes, which is in accordance with results of Miller et al (2022), where consumers rated chuck roasts lowest for overall, overall flavor, grilled flavor, and juiciness liking.…”
Section: Influence On Sensory Qualitysupporting
confidence: 88%
“…On the other hand, chuck steaks had the lowest scores for all sensory attributes, which is in accordance with results of Miller et al (2022), where consumers rated chuck roasts lowest for overall, overall flavor, grilled flavor, and juiciness liking.…”
Section: Influence On Sensory Qualitysupporting
confidence: 88%
“…These discrepancies could be explained by changes in the formulation and/or cooking method (cast-iron skillet vs. clamshell electric grill). Overall, the texture intensities of both GB and PBMA were relative to the intensities of 80/20 ground beef reported in Miller et al [ 14 ].…”
Section: Discussionmentioning
confidence: 68%
“…Kaczmarska, et al [ 12 ] reported plant-based protein and meat substitutes produced a greater diversity of volatile compounds compared to beef and other animal protein sources, which translated to the difference in sensory descriptors. The present study shows PBMA do not possess characteristic beef flavor aromatics; rather, they comprised other flavor aromatics that are not always detectable in beef, such as nutty, smokey-charcoal, and musty/earthy [ 13 , 14 ]. These results are congruent with the findings of Davis et al [ 11 ], who reported a clear difference in beef flavor identity between GB and PBMA.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, tenderness has been extensively studied [ 5 , 6 , 7 , 8 , 9 , 10 ]. However, other studies have suggested that flavor is just as important to consumers as tenderness [ 3 , 11 , 12 , 13 ]. It is well-established that the palatability characteristics of beef cuts can be influenced by a variety of antemortem and postmortem factors including animal diet [ 14 , 15 , 16 , 17 ], the use of growth promoting technologies [ 18 , 19 , 20 ], and postmortem aging [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%